The mill & the cross [videorecording (DVD)] - Gibson, Michael, 1929-2017; Majewski, Lech, 1953-; Hauer, Rutger, 1944-2019-; York, Michael, 1942-; Rampling, Charlotte, 1946- (Angelus Silesius, distributed by Kino Lorber, Inc., 2010)
Lech Majewski brings to life Pieter Bruegel's masterpiece The Way to Calvary, the story of the crucifixion, setting it in 16th century Flanders under brutal Spanish occupation.--Container.